Impactos de la deforestación e incendios forestales en la distribución potencial de especies forestales de aprovechamiento condicionado del bosque andino ecuatoriano - Rey Jumbo, Yessica Lisbeth (2023)
The Andean forests, in spite of having a great biodiversity and endemism, are the ecosystems most affected by anthropic actions such as deforestation and forest fires. For this reason, the objective of this research was to determine and provide information on the areas of suitability of the species of conditional use of the Andean Forest and how these have been affected by deforestation and forest fires. The suitability areas of six species (Cedrela montana Moritz ex Turcz, Clusia alata Triana & Planch., Clusia elliptica Kunth., Clusia multiflora Kunth., Ruagea glabra Triana & Planch. and Guarea kunthiana A. Juss.) by using presence records and the combination of bioclimatic variables. First, presence records were filtered in order to eliminate records without coordinates, duplicate coordinates, outliers and spatial correlation. Next, the areas of calibration and selection of bioclimatic variables were determined, taking into account their contribution and correlation. Subsequently, using R and MaxEnt software, the best candidate models were selected, evaluated and projected, resulting in a final binary with the species' suitability area, which was validated by specialists. To evaluate the areas of suitability affected by deforestation and forest fires, first the data on vegetation cover and records of active fires were downloaded. Then, a filtering of active fires was performed, eliminating records < 30 % reliability, volcanic zones and anthropic zones. To determine the deforested area, native forests were extracted from the vegetation cover shape, and an intersection was made with the adaptation areas and the deforestation shape. Similarly, the number of active fires in the area of suitability was obtained using an intersection. Finally, the species most affected by deforestation were Guarea kunthiana with a loss of 11.68 % of its suitability area, followed by Ruagea glabra with 11.12 %, and Clusia multiflora with 9.41 %. Meanwhile, the species most affected by forest fires were Clusia elliptica with 0.0013 AF/km2, followed by Clusia multiflora with 0.0088 AF/km2, and Cedrela montana with 0.0087 AF/km2. Thus, it is concluded that the modeling of species through MaxEnt and R, allows obtaining relevant information on the areas of suitability and spatial distribution of species, as well as obtaining statistics on how these have been degraded or affected over the years by anthropogenic factors such as deforestation and forest fires. These findings are crucial because they help to generate new measures for the conservation and management of the species and their habitat. Key words: Suitability, distribution, MaxEnt, deforestation, fires.